PENGARUH LITERASI KEUANGAN DAN GAYA HIDUP TERHADAP PENGELOLAAN KEUANGAN PADA GENERASI Z DI KOTA MEDAN DIMEDIASI OLEH PERILAKU KONSUMTIF - Putri, Linzzy Pratami; Christiana, Irma; Febriaty, Hastina; Safira, Mutiara (Universitas Muhammadiyah Tangerang, 2024)
Born in the modern era with easy access Generation Z was born in the modern era with easy access to technology which continues to develop resulting in ease of accessing all needs via the internet but because of this lifestyle. Generation Z has access to better technology than previous generations. Generation Z has a lack of financial management skills which causes them to experience difficulty in managing their finances. The aim of this research is to examine and analyze the influence of Financial Literacy and Lifestyle on Financial Management in Generation Z in Medan City, mediated by consumer behavior directly or indirectly. The approach used in this research is a quantitative approach. The population in this study is Generation Z located in Medan City with the districts of Medan Helvetia, Medan Marelan, East Medan, West Medan, Medan Deli whose numbers are unknown. The sample in this study used the Nonprobability Sampling method with an Incidental Sampling technique totaling 100 Generation Z people. The data collection technique in this research used a questionnaire technique. Data processing in this research uses the PLS (Partial Least Square) software program. The results of this research prove that Financial Literacy directly has a significant influence on Financial Management of Generation Z in Medan City, Lifestyle has a significant influence on Financial Management of Generation Z in Medan City, Financial Literacy has a significant influence on Consumer Behavior of Generation Z in Medan City, Lifestyle has a significant effect on Consumptive Behavior in Generation Z in Medan City, Consumptive Behavior has no significant effect on Financial Management in Generation Z in Medan City, Financial Literacy has no significant effect on Financial Management through Consumptive Behavior in Generation Z in Medan City, and Lifestyle has no effect significant impact on Financial Management through Consumptive Behavior in Generation Z in Medan City.